Trait Anxiety and Goal Difficulty on Learning to Climb the Bachman Ladder. Issue 2 (April 2014) - Neiva, Jaqueline F. O.; Massa, Marcelo; Barros, Joao A. C.; Meira, Cassio M.
This study examined the effects of trait anxiety and goal setting on learning of the Bachman ladder. It was hypothesized that easy goals would increase learning for individuals with high trait anxiety while hard goals would increase learning for individuals with low trait anxiety. 80 high school students (40 boys, 40 girls; M age = 15 yr., SD = 1.0) filled out the Brazilian State–Trait Anxiety Inventory (STAI) for trait anxiety. The experiment was divided into four phases: acquisition, immediate transfer (after 5 min.), delayed transfer, and retention (after 24 hr.). On the transfer phases, the participants started climbing the ladder with the foot opposite of that used in acquisition. Participants were assigned to one of four experimental groups combining high and low anxiety traits and hard and easy goals. Variances were analyzed with repeated measurements on the last factor of all phases. The results showed the performance increased during the acquisition phase and no effects were observed in any phases.